Handbook of Research on Healthcare Administration and Management. (Advances in healthcare information systems and administration (AHISA) book series., 2016)
"This book is a pivotal reference source for research material on emerging strategies and methods for delivering optimal healthcare opportunities and solutions, highlighting issues relating to decision making, process optimization, and technological applications"--Provided by publisher.